Selig airfoils: topology of flow patterns at low reynolds number - Che Ibrahim, Che Intan Hartini; Abdullah, Aslam (Asian Research Publishing Network (ARPN), 2021)
Over the years, extensive discussions on the flow topology have sparked a motivation for deeper studies on the process of vortex formation and the periodic behaviour of the reattachment profile. Despite a clear methodology, such flow topology studies have not yet covered the majority of airfoil types. This study considers three low Reynolds number Selig airfoils. The computational fluid dynamics simulations carried out involve the airflow passing these models. The attention is given mainly on the separation bubble, vortex shedding and reattachment point. The corresponding effects on airfoils aerodynamic performance are observed. The method is validated against an established mathematical relationship to indicate that both simulations and analysis technique are reliable. The results are applicable in micro aerial vehicles field where the airfoils are those of low Reynolds number.